Application for Recording Marriage Events at KUA: Design and Implementation Using Visual Studio 2012 and MySQL - Siska, Sri Tria; Suhery, Lilik; Hariyadi, Hariyadi; Ananda, Suci Rizki (Universitas Muhammadiyah Yogyakarta, 2024)
In the management of data recording marriage events at the KUA (the Office of Religious Affairs) is still manual and has not utilized information technology to the fullest. The process of inputting, managing and storing data on recording marriage events only utilizes Microsoft Office applications and there is even some data that is written manually so that the process of presenting reports for recording marriage events is still relatively slow and inefficient, there are often errors and loss of data which results in the KUA having to search for data again. To overcome this problem, an application design is carried out that can speed up the process of recording marriage events at the KUA. Design and Implementation was using Visual Studio 2012 and MySQL as a database processing place. The application designed to support the process of recording marriage events more effectively and efficiently.